DS‐8201a, a new HER2‐targeting antibody–drug conjugate incorporating a novel DNA topoisomerase I inhibitor, overcomes HER2‐positive gastric cancer T‐DM1 resistance. Issue 8 (12th July 2017) - Takegawa, Naoki; Nonagase, Yoshikane; Yonesaka, Kimio; Sakai, Kazuko; Maenishi, Osamu; Ogitani, Yusuke; Tamura, Takao; Nishio, Kazuto; Nakagawa, Kazuhiko; Tsurutani, Junji
Abstract : Anti‐HER2 therapies are beneficial for patients with HER2‐positive breast or gastric cancer. T‐DM1 is a HER2‐targeting antibody–drug conjugate (ADC) comprising the antibody trastuzumab, a linker, and the tubulin inhibitor DM1. Although effective in treating advanced breast cancer, all patients eventually develop T‐DM1 resistance. DS‐8201a is a new ADC incorporating an anti‐HER2 antibody, a newly developed, enzymatically cleavable peptide linker, and a novel, potent, exatecan‐derivative topoisomerase I inhibitor (DXd). DS‐8201a has a drug‐to‐antibody‐ratio (DAR) of 8, which is higher than that of T‐DM1 (3.5). Owing to these unique characteristics and unlike T‐DM1, DS‐8201a is effective against cancers with low‐HER2 expression. In the present work, T‐DM1‐resistant cells (N87‐TDMR), established using the HER2‐positive gastric cancer line NCI‐N87 and continuous T‐DM1 exposure, were shown to be susceptible to DS‐8201a. The ATP‐binding cassette (ABC) transporters ABCC2 and ABCG2 were upregulated in N87‐TDMR cells, but HER2 overexpression was retained. Furthermore, inhibition of ABCC2 and ABCG2 by MK571 restored T‐DM1 sensitivity. Therefore, resistance to T‐DM1 is caused by efflux of its payload DM1, due to aberrant expression of ABC transporters. In contrast to DM1, DXd payload of DS‐8201a inhibited the growth of N87‐TDMR cells in vitro . This suggests that either DXd may be a poor substrate of ABCC2 and ABCG2 in comparison to DM1, or the high DAR of DS‐8201a relative to T‐DM1 compensates for increased efflux. Notably, N87‐TDMR xenograft tumor growth was prevented by DS‐8201a. In conclusion, the efficacy of DS‐8201a as a treatment for patients with T‐DM1‐resistant breast or gastric cancer merits investigation. Abstract : What's new? In certain cancers, amplification and dysregulation of the human epidermal growth factor receptor HER2 is associated with more aggressive disease and worse prognosis, making it an appealing therapeutic target. Of special clinical interest in this regard is the antibody–drug conjugate (ADC) DS‐8201a, which consists of an anti‐HER2 antibody, a peptide linker, and an exatecan‐derivative topoisomerase I inhibitor (DXd). In the current preclinical study with gastric cancer cells, DS‐8201a was found to overcome resistance to T‐DM1, an established HER2‐targeting ADC, by upregulating the ATP‐binding cassette transporters ABCC2 and ABCG2. Moreover, the DS‐8201a Dxd payload successfully inhibited the growth of T‐DMI‐resistant cells.